Synergistic Literacies: Fostering Critical and Technological Literacies in Teaching a Legal Research Methods Course - Paul Havemann; Jacquelin Mackinnon (Legal Education Review)
[Extract] Public and professional discussion about the behaviour of lawyers is perennial to the point of cliché. Commentary about perceived inadequacies is also commonplace, but it is ordinarily based on anecdotal, though powerful, “war” stories. It seems, however, that legal educators and regulators must tackle the “ethics issue” with renewed vigour if legal institutions are to retain moral, and perhaps even spiritual, relevance. Ethics awareness projects are, of course, under way in many places (for example, the American Bar Association’s “Ethics 2000” programme); however, often they proceed with little direct information from the mass of legal practitioners as to their own perceived standards of conduct. As legal educators we can only design and teach ethics courses and help the legal profession describe the desirable attributes of the future lawyer using indirect information as to what is needed. My concern here is that legal ethics programmes, both in and after law school, may be proceeding on a comfortable, but possibly unfounded, assumption – that as legal educators or regulators we can simply appeal to the supposed better nature of our students and members in order to improve attitudes and, hence, behaviour. While, in my opinion, there is a link between lawyers’ attitudes/values and their behaviour, we first need to know about these attitudes and values.